Economic Assessment of Local Resource Integration of Ettawa Crossbreed Plants and Goats in Central Java - Fitriani, Rusita Fitriani; Umami, Nafiatul Umami; Kusumastuti, Tri Anggraeni (Universitas Halu Oleo, 2023)
Food security and self-sufficiency requires the use of local resources through plant-livestock integration. The purpose of the study was to assess the economic integration of goat farming and business fesibility . The research location is in Pamriyan Village, Pituruh District, Purworejo Regency. Determination of the sample by multistage purposive sampling as many as 60 farmers. Economic assessment of the integration of goat crops using the whole farm budget method, followed by business feasibility. The results showed that income from livestock crop integration in Pamriyan Village is IDR. 8,426,118/farmer//year. Plantation crops, horticulture, forestry contributed an average of IDR 7,2527,985/year (86.14%) and goats for IDR 1,1681.33 /farmer/year (13,86%). Goat farming is feasible with NPV amounting to IDR 7,446,202 , BCR 1.93 and IRR 39%.